Hardware simulator for frequency-watt control in smart inverters - Lee, Sun Hang; Cho, Sungjoon; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2021)
This paper presents a hardware simulator for a Frequency-Watt control in smart inverters. The power plant generator rotates at a constant speed, which is related to the frequency of the grid. The frequency of the grid is determined by the balance of power generation and power consumption. In addition, frequency fluctuations occur due to sudden changes in load or accidents. To reduce fluctuations and improve stability of grid system, the Frequency-Watt control in smart inverters was introduced. The PLL (Phase Locked Loop) control in various situations is important for grid-connected inverter to detect grid frequency. The real power limit of the smart inverter is controlled by the detected frequency to support grid stabilization. In this paper, the development of a hardware simulator for the Frequency-Watt control in smart inverters using three-level topology is introduced. The validity and performance of the proposed hardware simulator and its control strategies are demonstrated by various experimental results.
Keywords: Constant speed; Control strategies; Frequency fluctuation; Grid connected inverters; Grid frequency; Grid stabilizations; Hardware simulators; Smart inverters; Frequency-Watt control; Grid-connected inverter; Hardware-Simulator; Smart Inverter